Introducing a healthcare-assistive robot in primary care: a preliminary questionnaire survey - Tan, N. C.; Yusoff, Y.; Koot, D.; Lau, Q. C.; Lim, H.; Hui, T. F.; Cher, H. Y.; Tan, P. Y. A.; Koh, Y. L. E. (Frontiers in Robotics and AI, 2023)
A Healthcare-assistive Infection-control RObot (HIRO) is a healthcare-assistive robot that is deployed in an outpatient primary care clinic to sanitise the premises, monitor people in its proximity for their temperature and donning of masks, and usher them to service points. This study aimed to determine the acceptability, perceptions of safety, and concerns among the patients, visitors, and polyclinic healthcare workers (HCWs) regarding the HIRO. A cross-sectional questionnaire survey was conducted from March to April 2022 when the HIRO was at Tampines Polyclinic in eastern Singapore. A total of 170 multidisciplinary HCWs serve approximately 1,000 patients and visitors daily at this polyclinic. The sample size of 385 was computed using a proportion of 0.5, 5% precision, and 95% confidence interval. Research assistants administered an e-survey to gather demographic data and feedback from 300 patients/visitors and 85 HCWs on their perceptions of the HIRO using Likert scales. The participants watched a video on the HIRO’s functionalities and were given the opportunity to directly interact with it. Descriptive statistics was performed and figures were presented in frequencies and percentages. The majority of the participants viewed the HIRO’s functionalities favourably: sanitising (96.7%/91.2%); checking proper mask donning (97%/89.4%); temperature monitoring (97%/91.7%); ushering (91.7%/81.1%); perceived user friendliness (93%/88.3%), and improvement in the clinic experience (96%/94.2%). A minority of the participants perceived harm from the HIRO’s liquid disinfectant (29.6%/31.5%) and that its voice-annotated instructions may be upsetting (14%/24.8%). Most of the participants accepted the HIRO’s deployment at the polyclinic and perceived it to be safe. The HIRO used ultraviolet irradiation for sanitisation during after-clinic hours instead of disinfectants due to the perceived harm.